2009
DOI: 10.1111/j.1475-4983.2009.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

High European sauropod dinosaur diversity during Jurassic–Cretaceous transition in Riodeva (Teruel, Spain)

Abstract: Up to now, more than 40 dinosaur sites have been found in the latest Jurassic -earliest Cretaceous sedimentary outcrops (Villar del Arzobispo Formation) of Riodeva (Iberian Range, Spain). Those already excavated, as well as other findings, provide a large and diverse number of sauropod remains, suggesting a great diversity for this group in the Iberian Peninsula during this time. Vertebrae and ischial remains from Riodevan site RD-13 are assigned to Turiasaurus riodevensis (a species described in RD-10, Barrih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 45 publications
1
56
0
Order By: Relevance
“…This new information suggests a more diverse scenario for sauropod fauna during the Late Jurassic of the Lusitanian Basin than previously considered, with the identification of a clade previously unidentified in this basin, the non-neosauropod eusauropod group Turiasauria. Royo-Torres et al (2006) suggested the presence of Turiasauria in the Portuguese Upper Jurassic record, and this hypothesis was subsequently corroborated by the presence of new teeth and postcranial material (Mateus, 2009;Royo-Torres et al, 2009;Ortega et al, 2010;Mocho et al, 2012;Royo-Torres et al, 2014a;Mocho et al, 2016b). Four taxa, so far exclusively, were described in the Upper Jurassic of the Lusitanian Basin: the camarasaurid Lourinhasaurus alenquerensis (Lapparent and Zbyszewski, 1957;Dantas et al, 1998;Mocho et al, 2014b); the diplodocid Dinheirosaurus lourinhanensis (Bonaparte and Mateus, 1999;Mannion et al, 2012; recently referred as Supersaurus lourinhanensis by Tschopp et al, 2015), the basal macronarian and putative brachiosaurid Lusotitan atalaiensis (Lapparent and Zbyszewski, 1957;Antunes and Mateus, 2003;Mannion et al, 2013), and the turiasaur Zby atlanticus .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This new information suggests a more diverse scenario for sauropod fauna during the Late Jurassic of the Lusitanian Basin than previously considered, with the identification of a clade previously unidentified in this basin, the non-neosauropod eusauropod group Turiasauria. Royo-Torres et al (2006) suggested the presence of Turiasauria in the Portuguese Upper Jurassic record, and this hypothesis was subsequently corroborated by the presence of new teeth and postcranial material (Mateus, 2009;Royo-Torres et al, 2009;Ortega et al, 2010;Mocho et al, 2012;Royo-Torres et al, 2014a;Mocho et al, 2016b). Four taxa, so far exclusively, were described in the Upper Jurassic of the Lusitanian Basin: the camarasaurid Lourinhasaurus alenquerensis (Lapparent and Zbyszewski, 1957;Dantas et al, 1998;Mocho et al, 2014b); the diplodocid Dinheirosaurus lourinhanensis (Bonaparte and Mateus, 1999;Mannion et al, 2012; recently referred as Supersaurus lourinhanensis by Tschopp et al, 2015), the basal macronarian and putative brachiosaurid Lusotitan atalaiensis (Lapparent and Zbyszewski, 1957;Antunes and Mateus, 2003;Mannion et al, 2013), and the turiasaur Zby atlanticus .…”
Section: Introductionmentioning
confidence: 98%
“…Several new occurrences have also been reported (Antunes and Mateus, 2003;Mateus, 2005;Royo-Torres et al, 2006;Yagüe et al, 2006;Mateus, 2009;Royo-Torres et al, 2009;Ortega et al, 2010;Mannion et al, 2012;Mocho et al, 2012Mocho et al, , 2013aMocho et al, , 2013bMateus et al, 2014;Mocho et al, 2014aMocho et al, , 2016bMocho et al, , 2017. This new information suggests a more diverse scenario for sauropod fauna during the Late Jurassic of the Lusitanian Basin than previously considered, with the identification of a clade previously unidentified in this basin, the non-neosauropod eusauropod group Turiasauria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another tooth that is very similar in character to the Skye tooth is that assigned to the eusauropods Turiasauria and Neosodon as described by Royo-Torres et al (2009heartshaped crowns (when unworn), a pointed and asymmetrical crown apex that is strongly compressed labiolingually and tooth crowns with convex labial surfaces with a bulge that extends from the base towards the apex").…”
Section: <Figure 5>mentioning
confidence: 99%
“…Most of these dinosaurs were sauropods, and their sizes are comparable to those seen in other sauropod faunas (cf. Paul 1998;Henderson 1999;Seebacher 2001;Aberhan et al 2002;Mazzetta et al 2004;Carpenter 2006;Foster 2007;Lovelace et al 2007;Gunga et al 2008;Sander and Clauss 2008;Royo-Torres et al 2009;Taylor 2009;Klein et al in press).…”
Section: Introduction: Really Big Herbivoresmentioning
confidence: 99%